MODELLING OF EXTRUSION PROCESS FOR EVALUATION OF SPELT WHOLEGRAIN SNACK EXPANSION - Kojić, Jovana; Krulj, Jelena; Šimurina, Olivera; Cvetković, Biljana; Pezo, Lato; Đermanović , Branislava; Ilić Neboјša (Journal on Processing and Energy in Agriculture, 2021)
The effect of extrusion parameters, including feed rate (15–25 kg/h), screw speed (250–750 rpm) and feed moisture (15–25%) on expansion index of spelt wholegrain snack products was investigated. Wholegrain spelt flour was extruded using co-rotating twin-screw extruder (Bühler BTSK 30/28D, 7 sections, length/diameter ratio = 28:1, Bühler, Uzwil, Switzerland). The obtained data demonstrate that increased feed moisture leads to a decrease in the expansion of extrudates. An increase in screw speed resulted in lower viscosity of dough showing a higher elasticity, which have resulted in the higher expansion index. The highest expansion index (1.93) was achieved at the following operating conditions: screw speed (750 rpm), feed moisture (20%) and feed rate (20kg/h). The Yoon’s model has shown that screw speed has the greatest positive influence on the expansion index (approximately 60%). It is followed by negative influence of feed moisture, while the feed rate has an insignificant influence on the expansion index.